Globalization, health and health policy - Charalambous, Andreas; Socratous, Socrates; Charitou, Andreas (My University, 2011)
Aim: Review of the literature in terms of the consequences of globalization in the health care arena and the necessity of the involvement of international organizations in the development of international health policy. Method: A search was made in electronic databases for review and research studies on the consequences of globalization in the health care arena, using the keywords "globalization", "health", "policy", and "consequences". The search was extended to include the databases of the European Union (EU), the World Health Organization (WHO) and the United Nations (UN) for the last five years. Results: The review findings are contradictory, since the majority of the research studies show that the process of globalization has had beneficial results in the health care arena. The main positive effects include the evolution of technology developments in other sciences, which contribute to the rapid circulation of commodities and new accomplishments, facilitate communication and enhance the fight against disease. Other studies, however, illustrate the negative consequences of globalization, such as economic inequalities in the development of the different countries, and the spread of unemployment, poverty and social exclusion which are all closely interrelated with poor health and illness. The promotion of consumerism leads to the improvident use of natural resources and to ecological disaster, and jeopardizes the health of the consumers. In the political arena, many democratic institutions are undermined since the national centres of authority are not in full control of their financial policy and are obliged to adjust to the behests of international centres of control and worldwide influences. Conclusions: The perpetuation of the major health problems reflects on the responsibilities of the centres of power of the planet but also illustrate the weaknesses of the WHO, the UN and the EU and their inability to play a leading role in the development and implementation of an international health policy.
Keywords: Globalization; Health; Policy; Socio-economic consequences